Commons as Demanding Social Constructions: The Case of Aquifers in Rural Karnataka. (April 2021) - Landy, Frédéric; Ruiz, Laurent; Jacquet, Julie; Richard-Ferroudji, Audrey; Sekhar, M.; Guétat-Bernard, Hélène; Oger-Marengo, Marlène; Venkatasubramanian, G.; Noûs, Camille
It is only recently that research on Indian groundwater has considered a perspective in terms of commons. ATCHA, an interdisciplinary project that includes among others hydrology, crop modelling and remote sensing analysis, includes such a lens in its study of the Berambadi watershed, Karnataka, India. Participant observation, semi-structured interviews and focus groups have shown that the local aquifers are not managed as a commons, and brought into light several factors hindering collective action. In this paper, these factors are reconsidered, in particular through Ostrom's criteria. The national policy is currently trying to define a new legal framework for more sustainable management of the resource, but this new law is not known to users and it seems difficult to implement because it calls into question too many vested interests. We argue for aquifer management committees, which could be an intermediary between national policy orientations and users who are (rationally) not endorsing collective action.